A family of mixed-ligand oxidovanadium(v) complexes with aroylhydrazone ligands: a combined experimental and computational study on the electronic effects of para substituents of hydrazone ligands on the electronic properties, DNA binding and nuclease activities. Issue 112 (28th October 2015) - Patra, Debashis; Biswas, Nirmalendu; Kumari, Bhavini; Das, Prolay; Sepay, Nayim; Chatterjee, Shamba; Drew, Michael G. B.; Ghosh, Tapas
Abstract : Substituents at 5-position in the acetophenone ring of the hydrazone ligands in a family of mixed-ligand oxidovanadium(v ) complexes show marked influence on the electronic properties, DNA binding ability and nuclease activity. Abstract : A new series of mixed-ligand oxidovanadium(v ) complexes [V V O(HL 1–4 )(hq)] (1–4 ) have been synthesized using 2-hydroxybenzoylhydrazones of 2-hydroxyacetophenone and its 5-substituted derivatives (H3 L 1–4 ) along with 8-hydroxyquinoline (Hhq) as co-ligand. The complexes were characterized by elemental analyses, magnetic susceptibility measurements and various spectroscopic methods. Their electrochemical behaviour is also reported. X-ray crystallographic investigations of1–4 show the presence of distorted octahedral geometries with O4 N2 coordination environments for each of the four complexes. λ max values for the ligand-to-metal-charge-transfer (LMCT) transition, E ½ values and the chemical shift parameters ( δ ) for the 51 V NMR spectra of the complexes exhibit a linear relationship with the Hammett constant ( σ ) of the substituents. DFT methods were used to predict the bond lengths, bond angles, λ max values for electronic transitions and δ values of 51 V NMR spectra, all of which are found to be in good agreement with experimental results. The stability of the complexes was also examined. All the complexes exhibit DNA binding activity with CT-DNA either by minor groove binding mode (for1 and4 ) or by partial intercalation mode (for2 and3 ). The complexes were also tested for DNA nuclease activity with pUC19 plasmid DNA and were found to produce both nicked coiled and linear forms. The DNA binding and nuclease activities of the complexes follow the order:3 >2 >1 >4, which is also the hydrazone ligands' basicity order, suggesting that the binding and cleavage efficiencies are proportional to the electron density on the vanadium centre. The results of DNA binding experiments are further supported by molecular docking studies.